Antitumoral effect of green tea on oral squamous cell carcinoma: Integrative review (Research, Society and Development, 2021)
Objective: To evaluate the antitumor effect of green tea and its natural compounds on oral squamous cell carcinoma (OSCC). Methodology: This is an integrative literature review based on the guiding question “Does green tea have an anti-tumor effect on the development of OSCC?”. The search was carried out with the descriptors "Camellia sinensis", "Green tea"; "Oral cancer"; “Squamous cell carcinoma”; “Animals” and “anticarcinogenic agents” in the PubMed, Science Direct, Scielo and Google Scholar databases. The inclusion criteria were scientific articles on the effect of green tea, in the form of extract or isolated compounds, in the OSCC, in vivo studies, in any language. Results: A total of 1,245 articles were obtained, of which 11 were selected. Most studies (90.9%) were carried out by eastern countries. Epigallocatechin gallate, hamsters and DMBA were the most used compounds, animal model and carcinogen, respectively. There were several mechanisms of action (oxidative stress, apoptosis, inhibition of cell proliferation and differentiation) and molecular effects (alteration in the expression of glycoconjugates, amyloid precursor proteins, metalloproteinases and the formation of invadopodia) in green tea. Final considerations: Green tea has an anti-tumor effect on oral squamous cell carcinoma, exerting both chemopreventive and therapeutic action, by different routes. As it is a natural, biocompatible, safe and easily accessible/low cost product, its use should be explored in order to contribute to the treatment / prevention of OSCC, the most frequent type of oral cancer.